Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How do I find the pdf of $\prod_{i=1}^n X_i$, where $X_is$ are independent uniform [0,1] random variables.

I know X~U[0,1], -ln(x) is exponential(1). I also know the sum of two or more independent exponential random variable is gamma.

For $Y = \sum_{i=1}^n -ln(x_i)$, which is a gamma(n, 1), I found the pdf for Y is $$\int_0^\infty \frac{1}{\Gamma (n)} y^{n-1} e^{-y} dy$$.

Let $Z = e^Y$

I am trying to the pdf for Z, what I found is $$\int_1^\infty \frac{1}{\Gamma (n)} ln(z)^{n-1} \frac{1}{z^2} dz$$, which does not look right to me. Could someone check it?

share|improve this question
    
See this. –  Clement C. May 13 at 2:15
    
Thank you for the resource! The material is too math intensive –  afsdf dfsaf May 13 at 2:16
    
Can you rederive the result when $n=2$? (using this directly, for instance?) And for $n=3,4,...$ using the trick of taking the logarithm of the product, and computing the convolution of the pdfs of the logarithms of uniform r.v.'s? –  Clement C. May 13 at 2:22
    
Can you show me some steps? –  afsdf dfsaf May 13 at 2:23
    

2 Answers 2

up vote 2 down vote accepted

Step 1: Note that $-\log X_j$ has an exponential(1) distribution.

Step 2: Note that $\sum_{j=1}^n (-\log X_j)$ is a sum of iid random variables, so convolution results apply.

Step 3: Figure out the convolution for the exponential distribution, by looking it up, by using characteristic functions, or moment-generating functions, whichever you're familiar with. You'll find $f_X(x)=x^{n-1} e^{-x} / (n-1)!$ as the density of $-\log Y$, which is a $\Gamma$ distribution.

Step 4: Transform this back to get something like $(-\log y)^{n-1}/(n-1)!$.

Note that for increasing $g$ (decreasing $g$ is analogous), $$\Pr(Y\leq y)=\Pr(g(X)\leq y)=\Pr(X\leq g^{−1}(y))=F_X(g^{−1}(y)).$$

Now differentiate with respect to $z$ to get

$$ f_Y(y) = f_X(g^{-1}(y)) g^{-1}\;'(y)= \frac{f_X(g^{-1}(y))}{g'(g^{-1}(y))}. $$

In your case $g(x)=\exp(−x)$ which is decreasing in $x$ and hence you need to replace the denominator with $|g′(g^{−1}(y))|$.

So $g'(x)=-\exp(-x)$ and $g^{-1}(y)=-\log y$.

share|improve this answer
    
what is the " convolution results "? –  afsdf dfsaf May 13 at 3:55
    
Convolutions are standard results that give you the distribution of a sum of two or more iid random variables. –  JPi May 13 at 3:59
    
Can you be a little bit more explicit on step 3? –  afsdf dfsaf May 13 at 18:25
1  
Don't integrate. The density function is the integrand, not the integral. Aside from that, I think it should be $Z=e^{-Y}$. By the standard change of variable formula for density functions I get for $y= -\log z$ that $$y^{n-1} e^{-y} / (\Gamma(n) e^{-y}) = (-\log z)^{n-1}/(n-1)!$$ Hope this helps. –  JPi May 15 at 12:59
1  
how do you make that to become $(-\log y)^{n-1}/(n-1)$? –  afsdf dfsaf May 15 at 15:55

An attempt:

For the case $n=2$, using directly the fact that (for $Y=X_1X_2$, where $X_1,X_2\sim\operatorname{Unif}([0,1])$ are independent) $$ \forall z\in[0,1],\quad f_Y(z)=\int_0^1 f_{X_1}(x)f_{X_2}\left(\frac{z}{x}\right)\frac{dx}{x} $$ you get that for all $z\in(0,1]$ $$ f_Y(z)=\int_0^1 1\cdot \mathbb{1}_{\{\frac{z}{x}\in[0,1]\}}\frac{dx}{x} = \int_z^1 \frac{dx}{x} = \ln\frac{1}{z} $$

For the general case, you can apply the trick of taking the logarithm of $Y=\prod_{k=1}^n X_k$, i.e. consider $Z\stackrel{\rm def}{=} \ln Y = \sum_{k=1}^n \ln X_k = \sum_{k=1}^n Z_k$ for $Z_k\stackrel{\rm def}{=} \ln X_k$, so that for all $z\in(-\infty,0]$ $$ f_Z(z)=(f_{X_1}\ast\cdot\ast f_{X_k})(z) = (f_{X_1}\ast\cdot\ast f_{X_1})(z) $$ where $\ast$ is the convolution operator and $$ \begin{align*} f_{X_1}(x) &= \frac{d}{dx}\int_{-\infty}^x \mathbb{P}\left\{\ln X_1 \in dt\right\} = \frac{d}{dx} \mathbb{P}\left\{\ln X_1 \leq x\right\}= \frac{d}{dx} \mathbb{P}\left\{X_1 \leq e^x\right\}\\ &= \frac{d}{dx}\mathbb{P}\left\{X_1 \leq e^x\right\}= \frac{d}{dx} e^x = e^x \end{align*} $$ (caveat: I haven't carefully checked my calculations) Once (after a lot of fun) you figure $f_Z$, you can go back to $f_Y$ by a similar process (using the cdf of $f_Z$, etc).

share|improve this answer
    
I just realized If X~U[0,1], -ln(x) is exponential(1)...Does this help reduce the work? –  afsdf dfsaf May 13 at 2:44
    
This is essentially what the last computation above shows (the one ending with $e^x$). –  Clement C. May 13 at 2:46

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.